Modiano Historien - Richard J. Golsan (Studies in 20th & 21st Century Literature, 2007)
Beginning with the "Trilogy" (La place de l'étoile, Ronde de nuit, and Les boulevards de ceinture) of his first three novels published in the late 1960s and early 1970s, the work of Patrick Modiano has been indissociably linked with the history and memory of the Occupation. Dora Bruder is of course no exception along these lines. What makes Modiano's Occupation novels distinctive is their combination of the "historian's" knowledge of the historical realities of the period and the novelist's or "poet's" talent for powerfully evoking the feel and ambiance of "les années noires." While Modiano's practice as novelist has been widely discussed, his practice and especially his vision as "historian" deserves greater attention. This essay seeks to assess the novelist's historical vision through a reading of Dora Bruder, including the "Trilogy" and the more recent Un pedigree.
Keywords: La place de l& #x27; étoile; Ronde de nuit; Les boulevards de ceinture; Patrick Modiano; Occupation; Dora Bruder; Holocaust; history; un pedigree